Legionellosis in Spain, 2010-2015 - Gea-Izquierdo, Enrique (Biomedica, 2021)
Introduction: Legionellosis is a bacterial respiratory disease with an environmental origin in the community or in hospitals; it is usually associated with devices, facilities, and buildings. The most common clinical form is the pneumonic, known as legionnaires’ disease. Objective: To determine the evolution of legionellosis cases in Spain from 2010 to 2015. Materials and methods: This was a descriptive study of time series with an analysis of the legionellosis cases notified to the Centro Nacional de Epidemiología (Government of Spain). Case distribution was determined according to sex, the autonomous community of origin, month, and age groups differentiating in the latter between men and women. Results: Case count in men was more than double compared to that in women. The cases notified by nine of the autonomous communities showed an increase at the end of the period, especially in Castilla y León, Navarra, and the Basque Country but also notable in Castilla-La Mancha. A seasonal pattern was identified with an epidemic peak in July-September and a greater number of cases among 50-years old people from both sexes. Conclusion: Despite its low prevalence compared to other respiratory diseases, legionellosis has a great impact on public health. Its distribution in Spain is global and heterogeneous with cases increasing in the last two years. Therefore, better disease prevention and control measures are recommended.